Neuregulin1 Fine-tunes Pre-, Post-, and Peri-Synaptic Neuromuscular Junction Development - Wang, Jiajing (Dev Dyn, 2017)
BACKGROUND: Neuromuscular junction (NMJ) development is a multistep process mediated by coordinated interactions between the nerve terminal, target muscle, and perisynaptic Schwann cell that require constant back-and-forth communication. Retrograde and anterograde growth and differentiation factors have been postulated to participate in this communication. While neuregulin1 (NRG1) has been shown to be potent anterograde signal that activates acetylcholine receptor (AChR) transcription and clustering in vitro, its roles in NMJ development in vivo remain elusive. RESULTS: Using the model of chicken embryo, we measured the effects of NRG1 signaling during NMJ development in ovo using quantitative, sequential measures of AChR cluster size and density, pre- and post-synaptic apposition, and the alignment of perisynaptic Schwann cells. Using in ovo electroporation at early stages and a targeted soluble neuregulin antagonist through all developmental stages, we found soluble NRG1 regulates AChR cluster density and size at the earliest stage prior to nerve-AChR cluster contact. Once the nerve contacts with muscle AChRs, NRG1 has pronounced effects on presynaptic specialization and on the alignment of perisynaptic Schwann cells at endplates. CONCLUSION: These findings suggest that, while NRG1 may not be critical for overall development, it appears to be important in fine-tuning pre-, post-, and peri-synaptic development of the NMJ.